The Molecular Evolution of Xenobiotic Metabolism and Resistance in Chelicerate Mites - Van Leeuwen, Thomas; Dermauw, Wannes (Annual review of entomology, 2016)
Chelicerate mites diverged from other arthropod lineages more than 400 million years ago and subsequently developed specific and remarkable xenobiotic adaptations. The study of the two-spotted spider mite, Tetranychus urticae, for which a high-quality Sanger-sequenced genome was first available, revealed expansions and radiations in all major detoxification gene families, including P450 monooxygenases, carboxyl/cholinesterases, glutathione-S-transferases, and ATP-binding cassette transporters. Novel gene families that are not well studied in other arthropods, such as major facilitator family transporters and lipocalins, also reflect the evolution of xenobiotic adaptation. The acquisition of genes by horizontal gene transfer provided new routes to handle toxins, for example, the β-cyanoalanine synthase enzyme that metabolizes cyanide. The availability of genomic resources for other mite species has allowed researchers to study the lineage specificity of these gene family expansions and the distinct evolution of genes involved in xenobiotic metabolism in mites. Genome-based tools have been crucial in supporting the idiosyncrasies of mite detoxification and will further support the expanding field of mite-plant interactions.